Analysis of Bone Mineral Density and Bithermal Caloric Test Results in Unilateral Idiopathic Benign Paroxysmal Positional Vertigo Patients. Issue 7 (29th August 2022) - Jiang, Xiuwen; Ding, Haibing; Shen, Bin; Wu, Ziying; Luo, Baozhen
Abstract : Objective: Benign paroxysmal positional vertigo (BPPV) is the most frequently diagnosed type of peripheral vestibular vertigo. Studies have reported a possible association between BPPV and osteoporosis; however, there is still a lack of evidence. This study aimed to investigate the characteristics of bone mineral density (BMD) and bithermal caloric test results in patients with unilateral posterior canal idiopathic benign paroxysmal positional vertigo (pc-iBPPV). Methods: BMD was measured in 65pc-iBPPV menopausal female patients and 65 healthy controls using dual-energy xray absorptiometry and then compared the T-score of BMD between the two groups. The bithermal caloric test was also performed with video nystagmography and the relationship between canal paresis, directional preponderance, T-score, and recurrence were analyzed. Results: Lower T-scores were observed in pc-iBPPV patients compared with the normal subjects. Among 65 pc-iBPPV patients, free recurrence was observed in 38 (58.5%), single recurrence was noted in 14 (21.5%), and multiple recurrences were seen in 13 (20%) patients. The proportion of positive T-score and CP value increased with the pc-BPPV recurrence frequency. Statistically, a significant difference was found only in T-score, indicating that recurrence was raised with a decrement of T-score. The proportion of positive CP values tended to increase as BMD decreased. Conclusion: The decrement of BMD might be one of the pathogeneses in patients with unilateral pc-iBPPV and associated with multiple recurrences. Moreover, positive CP value cannot be regarded as a predictive factor for recurrence; however, there is a clear association between CP and BMD.